2016
DOI: 10.5194/acp-16-14959-2016
|View full text |Cite
|
Sign up to set email alerts
|

Significant concentrations of nitryl chloride sustained in the morning: investigations of the causes and impacts on ozone production in a polluted region of northern China

Abstract: Abstract. Nitryl chloride (ClNO2) is a dominant source of chlorine radical in polluted environment, and can significantly affect the atmospheric oxidative chemistry. However, the abundance of ClNO2 and its exact role are not fully understood under different environmental conditions. During the summer of 2014, we deployed a chemical ionization mass spectrometer to measure ClNO2 and dinitrogen pentoxide (N2O5) at a rural site in the polluted North China Plain. Elevated mixing ratios of ClNO2 (> 350 pptv) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
141
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 73 publications
22
141
5
Order By: Relevance
“…The average (±1σ ) ratio of ClNO 2 /N 2 O 5 was 6.9 ± 7.4, consistent with previous studies in NCP, for example 0.4-131.3 in Jinan and Wangdu (X. Tham et al, 2016). However, the ratios are substantially higher than those measured in other megacities, e.g., Hong Kong (0.1-2.0; Wang et al, 2016), London (0.02-2.4;Bannan et al, 2015), and Los Angeles, California (0.2-10.0; Mielke et al, 2013).…”
Section: Relationship Between N 2 O 5 and Clnosupporting
confidence: 78%
See 3 more Smart Citations
“…The average (±1σ ) ratio of ClNO 2 /N 2 O 5 was 6.9 ± 7.4, consistent with previous studies in NCP, for example 0.4-131.3 in Jinan and Wangdu (X. Tham et al, 2016). However, the ratios are substantially higher than those measured in other megacities, e.g., Hong Kong (0.1-2.0; Wang et al, 2016), London (0.02-2.4;Bannan et al, 2015), and Los Angeles, California (0.2-10.0; Mielke et al, 2013).…”
Section: Relationship Between N 2 O 5 and Clnosupporting
confidence: 78%
“…High levels of ClNO 2 from anthropogenic chloride sources were also reported in some inland areas (Thornton et al, 2010;Mielke et al, 2011;Phillips et al, 2012Phillips et al, , 2016Bannan et al, 2015). More recently some studies in Hong Kong Brown et al, 2016a;Wang et al, 2016) and in the North China Plain (NCP; Tham et al, 2016;Wang et al, 2018) observed consistently high mixing ratios of N 2 O 5 and ClNO 2 . In particular, ClNO 2 can be rapidly formed in the plumes of coal-fired power plants in the NCP, which serves as an important source of chloride in non-ocean regions.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Water-soluble ions were analyzed by a gas aerosol collector-ion chromatography (GAC-IC) system. More information on the site and instruments may be found in Tham et al (2016). The fourth sampling site was located near the summit of Mt.…”
Section: Introductionmentioning
confidence: 99%